2010
DOI: 10.1166/jnn.2010.2831
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun PCL/PLA/HA Based Nanofibers as Scaffold for Osteoblast-Like Cells

Abstract: Polycaprolactone (PCL), poly (lactic acid) (PLA) and hydroxyapatite (HA) are frequently used as materials for tissue engineering. In this study, PCL/PLA/HA nanofiber mats with different weight ratio were prepared using electrospinning. Their structure and morphology were studied by FTIR and FESEM. FTIR results demonstrated that the HA particles were successfully incorporated into the PCL/PLA nanofibers. The FESEM images showed that the surface of fibers became coarser with the introduction of HA nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 10 publications
4
33
0
Order By: Relevance
“…Moreover, HA has the potential to induce hMSCs differentiation into osteogenesis without any addition of growth factors and increase the ALP activity along with osteocalcin expression and mineralization [131]. It also enhances the surface topography of the scaffolds, promotes the growth of cells, adhesion, proliferation and differentiation [132][133][134]. The fabrication of Chitosan/HA biocomposite substitutes for bone tissue formation revealed that spherulites containing calcium and phosphorus is the major component in calcium phosphate apatite known as mineral phase of bone.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Moreover, HA has the potential to induce hMSCs differentiation into osteogenesis without any addition of growth factors and increase the ALP activity along with osteocalcin expression and mineralization [131]. It also enhances the surface topography of the scaffolds, promotes the growth of cells, adhesion, proliferation and differentiation [132][133][134]. The fabrication of Chitosan/HA biocomposite substitutes for bone tissue formation revealed that spherulites containing calcium and phosphorus is the major component in calcium phosphate apatite known as mineral phase of bone.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As temporary templates for cell seeding, migration, proliferation, and differentiation prior to the regeneration of natural extracellular matrix (ECM) or biological functional tissue, 2,3 biomaterial scaffolds for bone tissue engineering applications require consideration of proper toughness for cell adhesion, porous three-dimensional structure for cell migration and new bone tissue ingrowth, as well as good osteoconductivity to promote bone repair. 4,5 In recent years, electrospun fibers as bone scaffolds have received great attention for the following reasons: (1) their morphologies are similar to the structures of natural ECM, (2) their intrinsic large surface area-to-volume ratios offer sufficient space for cell adhesion and proliferation, and (3) their interconnected porous structures can provide windows for nutrient and metabolic waste exchange, 6,7 as well as promote vascularization to apply nutrient and drain the consumed metabolites in vivo. 8 The electrospinning technique was originally developed by Zeleny in 1914, 9 and was first patented in the 1930s.…”
Section: Introductionmentioning
confidence: 99%
“…42 The higher cell viability for the PEG/PLA electrospun fibrous scaffolds demonstrates that the electrospinning scaffolds can accelerate initial attachment of the cells and promote cells to penetration into fiber substrates, which is important for the application of biomaterial scaffolds. 4,33 In order to further confirm cytocompatibility of the PEG/PLA electrospun fibrous scaffolds, fluorescent microscopic images of MSCs grown on the scaffolds were taken. As shown in Figure 4, the cells were observed to adhere and spread actively with a physiological adherence pattern on both the tissue culture plate and the fibrous scaffolds.…”
mentioning
confidence: 99%
“…It can be blended with collagen or other biodegradable polymers such as gelatin with enhanced tissue regenerative properties [128,129]. Moreover, biomimetic and osseoconductive materials such as nano-sized hydroxyapatite (nano-HA) crystals can be incorporated to PCL-PLA fibers to produce composite scaffolds [130]. Additionally, incorporation of nano-HA crystals not only increases the osteogenic potential of these scaffolds but it has also been suggested that these scaffolds have mechanical properties superior to those made of PCL alone [131].…”
Section: Electrospun Nanofibers For Dental Applicationsmentioning
confidence: 99%